A novel homozygous frameshift mutation likely causing nonsense-mediated mRNA decay in an Algerian kindred with CD19 complex deficiency - Belaid, Brahim; Chan, Koon-Wing; Lamara Mahammed, Lydia; Leung, Daniel; Makhloufi, Sara; Bendaoud, Fadila; Sakhri, Hassiba; Berkani, Lilya Meriem; Allam, Ines; Merah, Fatma; Baaziz, Hadda; Lo, Bernice; et al. (Frontiers in Immunology, 2025)
BackgroundCD19 is an essential component of a membrane protein complex on B cells, which also includes complement receptor 2 (CD21), CD81, and CD225. It amplifies B cell receptor (BCR) signaling by recruiting regulatory molecules and facilitating the phosphorylation of key kinases. Mutations in the CD19 gene disrupt the integrity of this complex and impair BCR signaling, ultimately leading to antibody deficiency.Purposewe report here a novel mutation in the CD19 gene in two patients from consanguineous Algerian kindred.MethodsWe conducted a comprehensive analysis of the clinical, genetic, and immunological characteristics of two siblings with CD19 deficiency.ResultsBoth siblings began experiencing upper and lower respiratory tract infections in early childhood. Over time, the older sibling developed recurrent fungal and viral skin infections, as well as episodes of pyelonephritis. Whole exome sequencing identified a novel homozygous mutation in the CD19 gene, leading to an out-of-frame translation predicted to trigger nonsense-mediated decay and result in absent gene expression. Flow cytometry revealed a complete absence of CD19 and reduced CD21 expression on CD20+ B cells in both siblings, while CD81 expression remained normal. Despite normal total peripheral B cell counts, the older patient exhibited reduced memory B cells. Additionally, both patients displayed circulating autoantibodies and an increased frequency of circulating follicular helper T cells.ConclusionThese findings highlight the critical role of CD19 not only in the initial activation of B lymphocytes by T-dependent antigens, but also in the maturation and/or selection of activated B cells within the memory compartment.